Evaluation of the Feasibility and Utility of a Pharmacist-Centered Collaborative Drug Therapy Management Program for Oncology-Based Symptom Management. (June 2016) - Hansen, Elizabeth A.; Pietkiewicz, John M.; Blum, Bonnie L.
Collaborative drug therapy management (CDTM) is a practice agreement between a pharmacist and a physician, which allows the pharmacist to assume responsibility of drug therapy management. There has been limited documentation of CDTM practices in the oncology setting. Therefore, a CDTM program in the gynecology oncology clinic at Roswell Park Cancer Institute (RPCI) was initiated to establish the feasibility and utility of CDTM and its effects on patient care and physician satisfaction. Primarily, 3 symptoms were managed by the CDTM pharmacists, namely chemotherapy-induced nausea and vomiting (CINV), chemotherapy-induced peripheral neuropathy (CIPN), and women's health. The CDTM program showed favorable results after a short 4-month period. The CDTM pharmacists were referred a total of 12 consultations for CDTM purposes; 8 patients enrolled in the CIPN CDTM protocol, 3 in the CINV protocol, and 1 in the women's health protocol. The CDTM pharmacists were able to perform a total of 54 consultations, with a mean time of 16.9 minutes spent with each patient per consultation. Additionally, the CDTM pharmacists made 70 interventions and identified 6 medication-related adverse effects. The patient and physician satisfaction survey demonstrated the value of the CDTM pharmacists, and respondents were supportive of the program.